JENIS- JENIS AMPHIBIA YANG DITEMUKAN DI KEBUN KELAPA SAWIT KANAGARIAN KUNANGAN PARIK RANTANG KABUPATEN SIJUNJUNGMahasiswa Program Studi Pendidikan Biologi STKIP PGRI Sumbar - Silfiana, Vella - (Pendidikan Biologi, 2014)
Changes in forest conditions can cause negative impacts on the surrounding community as well as on biodiversity. Loss of habitat and wetlands in the processing of the garden as well as the inclusion of chemical compounds into the environment may pose a risk of animal extinction threat, one of Amphibia. Therefore, study on the types of Amphibia found in Kanagarian Kunangan Parik Rantang Sijunjung district palm oil plantations has been done,in order to determine the types of Amphibia in palm oil plantations. The study was conducted on 14 to 29 August 2014. This study was conducted using Visual ecounter survey (VES) method that is walking observation and survey directly toward Amphibia species obstained in the site, which is accompanied by some morphological characters measurement and description establishment. Observations were made in three habitats are puddles, rivers and oil palm verge. The result of the research showed 13 species with total 91 specimens Amphibians species had been collected which was consist of five families i.e. Bufonidae (Ingerophrynus biporcatus Gravenhorst., Phrynoidis asper Gravenhorst., Duttaprynus melanostictus Schneider.), Microhylidae (Microhyla heymonsii Vogt., Kaloula baleata Muller., Kalophrynus pleurostigma Tschudi.), Dicroglossidae (Fejervarya limnocharis Boie., Limnonectes blythi Boulenger.), Ranidae (Hylarana nicobariensis Stolizka, Hylarana erythraea Schlegel., Hylarana glandulosa Boulenger., Hylarana parvaccola Inger.), Rhacoporidae (Polypedates leucomystax Gravenhorst.).